Photoacid-macroion assemblies: how photo-excitation switches the size of nano-objects - Zika, Alexander; Agarwal, Mohit; Zika, Wiebke; Guldi, Dirk Michael; Schweins, Ralf; Gröhn, Franziska (Nanoscale, 2023)
Electrostatic self-assembly of photoacids with oppositely charged macroions yields supramolecular nano-objects in aqueous solutions, whose size is controlled through light irradiation. Nano-assemblies are formed due to electrostatic attractions and mutual hydrogen bonding of the photoacids. Irradiation with UV light leads to the deprotonation of the photoacid and, consequently, a change in particle size. Overall, the hydrodynamic radii of the well-defined photoacid-macroion nano-objects lie between 130 and 370 nm. For a set of photoacids, we determine the acidity constants in the ground and excited state, discuss the sizes of photoacid-macroion nano-objects (by dynamic and static light scattering), their composition and the particle shapes (by small-angle neutron scattering), and relate their charge characteristics to size, structure and shape. We investigate the association thermodynamics and relate nanoscale structures to thermodynamics and, in turn, thermodynamics to molecular features, particularly the ionization energy of the photoacid hydroxyl group proton. Structure-directing effects completely differ from those for previously investigated systems, with hydrogen bonding and entropic effects playing a major role herein. This combined approach allows developing a comprehensive understanding of assembly formation and photo-response, anchored in molecular parameters (pKa, ionization energy, substituent group location), charge characteristics, and the association enthalpy and entropy. This fundamental understanding again paves the way for tailoring application solutions with novel photoresponsive materials.
CRIS-Team Scopus Importer:2023-12-29